Human milk oligosaccharide metabolism and antibiotic resistance in early gut colonizers: insights from bifidobacteria and lactobacilli in the maternal-infant microbiome - Anna Samarra; Simone Renwick; Aleksandr A. Arzamasov; Dmitry A. Rodionov; Kennedy Spann; Raul Cabrera-Rubio; Antia Acuna-Gonzalez; Cecilia Martínez-Costa; Lindsay Hall; Nicola Segata; Andrei L. Osterman; Lars Bode; et al. (Gut Microbes, 2025)
Breast milk, rich in human milk oligosaccharides (HMOs), supports the early-life colonization of beneficial bacteria such as bifidobacteria and lactobacilli, potentially reducing early-life antibiotic resistance. However, antibiotic treatment may interfere with the beneficial functions of HMO-degrading bacteria. This study investigated the metabolism of HMOs by bifidobacteria and lactobacilli isolated from human milk and mother-infant paired fecal samples, along with their antibiotic resistance profiles. Understanding these species- and sample-type-specific interactions will provide valuable insights into how bioactive components in human milk may shape the infant resistome during early life. A total of 39 Bifidobacterium and 14 Lactobacillaceae strains were isolated from paired mother-infant fecal and breast milk samples. Whole genome sequencing (WGS) allowed functional predictions on the HMO metabolism abilities and the resistance genotype of each strain. In vitro HMO utilization was assessed using growth kinetics assays combined with HMO glycoprofiling in culture supernatant. The minimum inhibitory concentration (MIC) was also determined for each strain. HMO metabolism by the bifidobacteria was species-specific. Bifidobacterium bifidum (B. bifidum) and Bifidobacterium longum subsp. infantis (B. infantis) exhibited the highest capacity for HMO degradation, consistent with genomic predictions. In contrast, lactobacilli were unable to degrade HMOs in vitro but were predicted to metabolize the by-products of HMO degradation. Phenotypic analysis revealed that B. bifidum strains had the lowest levels of antibiotic resistance, while Bifidobacterium animalis subsp. lactis (B. lactis) strains were resistant to most tested antibiotics. Overall, B. bifidum demonstrated the strongest HMO-degrading ability while remaining the most antibiotic-susceptible species. Early-life colonizing bifidobacterial species possess the essential machinery required to degrade HMOs and are highly susceptible to antibiotics. A better understanding of these dynamics could inform clinical strategies to protect and restore the infant gut microbiome, particularly in neonates exposed to antibiotics.